Associated factors of undernutrition in children with congenital heart disease: a cross-sectional study - Ruan, Xiaorui; Ou, Jun; Chen, Yige; Diao, Jingyi; Huang, Peng; Song, Xinli; Wei, Jianhui; Sun, Mengting; Shi, Hongqiang; Li, Liuxuan; Tang, Jiapeng; Liu, Hanjun; et al. (Frontiers in Pediatrics, 2024)
Objective: To evaluate the prevalence and associated factors of undernutrition among children with congenital heart disease (CHD) who have not undergone surgeries in China. Methods: This cross-sectional study included 734 CHD children along with their parents. The outcome of interest was undernutrition, including underweight, wasting, and stunting, defined as Z-scores (i.e., weight-for-age, weight-for-height, and height-for-age) ≤-2, according to the World Health Organization (WHO) growth standard. Exposures of interest, containing demographics, obstetric factors, maternal dietary factors, parents’ life behaviors and habits, birth-related factors, cardiac-related factors, and preoperative factors, were analyzed using a multivariate logistic regression model to test their associations with undernutrition in CHD children. Results: Overall, 36.1%, 29.7%, and 21.3% of cases were underweight, wasted, and stunted, respectively. Multivariate logistic regression indicated that underweight was associated with demographic factors (including parents’ occupational status, family income, and maternal body mass index pre-pregnancy), low birth weight (OR=4.60, 2.76-7.70), pulmonary hypertension (OR=4.46, 3.09-6.43), and pneumonia (OR=1.88, 1.28-2.76). Artificially-fed children were 2.34 (1.36-4.01) times more likely to be underweight. Occupied mothers (OR=0.62, 0.44-0.88) and fathers (OR=0.49, 0.26-0.92) served as protective factors, while mothers having gestational complications (OR=1.56, 1.11-2.18) and exposed to noisy environment (OR=1.64, 1.11-2.42) during this pregnancy, and pulmonary hypertension (OR=3.21, 2.30-4.49) increased the chance of wasting in offspring. The odds of being stunted were greater in families with >2 children (OR=1.88, 1.13-3.14), placental abruption during this pregnancy (OR=25.15, 2.55-247.89), preterm births (OR=1.84, 1.02-3.31), low birth weight (OR=3.78, 2.16-6.62), pulmonary hypertension (OR=2.35, 1.56-3.53) and pneumonia (OR=1.93, 1.28-2.90). In subgroup analyses, the associations differed between patients with different feeding patterns (breastfeeding vs. non-breastfeeding), CHD classifications (cyanotic vs. acyanotic), and prematurity (preterm vs. non-preterm). Conclusion: Undernutrition is common in preoperative CHD children. Familial demographics, maternal factors (including having gestational complications and exposure to noisy environment during pregnancy), and patient-related factors (encompassing preterm births, low birth weight, pulmonary hypertension, pneumonia, and feeding pattern) were found to contribute to undernutrition in CHD cases. However, associated factors among the three subgroups of distinct feeding patterns, CHD categorization, and prematurity exhibited varied outcomes, suggesting the necessity for targeted interventions.